International transactions of the United States (1946-1968) - R. MOSSÉ (PSL Quarterly Review, 2014)
In spite of the extensive literature on the deficit in the US balance of payments, there is a great deal of confusion on the subject. In the present article, the authors propose to concentrate on the presentation of the facts from 1946 to 1968 in a form which will permit of a searching economic analysis. This approach brings out a better understanding of the transactions between the United States and the rest of the world. This method involves the use of several accounts and sub-accounts as well as the calculation of different types of balances. Three main types of accounts are examined separately: the current transactions account; the capital transactions account; and the account for settlements or offsetting transactions.